2004
DOI: 10.1111/j.1365-2966.2004.07162.x
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of accretion disc corona size in LMXB: consequences for Comptonization and LMXB models

Abstract: We present results of measurements of the radial extent of the accretion disc corona in low mass X-ray binaries, i.e. of the radial extent of the thin, hot ADC above the accretion disc. These results prove conclusively the extended nature of the ADC, with radial extent varying from 20,000 km in the faintest sources to 700,000 km in the brightest, a substantial fraction of the accretion disc radius, typically 15 per cent. This result rules out the Eastern model for LMXB which is extensively used, in which the C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
82
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(92 citation statements)
references
References 52 publications
9
82
1
Order By: Relevance
“…Recently, a different model has been proposed based on the idea of an extended accretion disc corona (ADC, Church & Balucinska-Church 1995;Church & Ba lucińska-Church 2004;Church et al 2012). In this modelṀ increases as the source moves upward along the NB track (the opposite of the Psaltis et al 1995 model).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a different model has been proposed based on the idea of an extended accretion disc corona (ADC, Church & Balucinska-Church 1995;Church & Ba lucińska-Church 2004;Church et al 2012). In this modelṀ increases as the source moves upward along the NB track (the opposite of the Psaltis et al 1995 model).…”
Section: Introductionmentioning
confidence: 99%
“…This work establishes that in the dip sources in general, the dominant Comptonized emission is removed slowly showing that the emission is extended, while the point-like blackbody emission which we associate with the neutron star is rapidly removed, and causes rapid variability in dipping. Measurement of dip ingress times allows the size of the extended emitter to be measured, and this has shown the ADC to reach over a large part of the inner accretion disk, have a radial extent R between 20 000 and 700 000 km, and is thin, with height H having H/R 1 (Church & Bałucińska-Church 2004). Strong independent support for the extended ADC comes from the Chandra grating results of Schulz et al (2009) in which emission lines of highly ionizied species were found to originate at radial distances between 20 000 and 110 000 km in an extended ADC.…”
Section: Introductionmentioning
confidence: 99%
“…These spectra were fitted using the extended ADC emission model so that the non-dip spectrum was fitted by a model of the form abs * (bb + cut), where abs is the Galactic absorption, bb the neutron star blackbody emission and cut the Comptonized emission of an extended ADC (Church & Bałucińska-Church 2004). In fitting, the Xspec model phabs was used as a more accurate form than the generally used wabs model.…”
Section: Spectral Fitting Of Epic-pn Spectramentioning
confidence: 99%
“…Spectral evolution during dipping can be explained in terms of point-like blackbody emission from the neutron star and the dominant Comptonized emission of an extended ADC (Church & Bałucińska-Church 1997). The extended nature of the ADC is shown by measurement of dip ingress times giving sizes of 20 000−700 000 km depending on luminosity (Church & Bałucińska-Church 2004). Strong support for an extended ADC comes from Chandra high-resolution grating results ) for highly excited H-like lines of Ne, Mg, Si, S and Fe in Cygnus X-2, with Doppler widths corresponding to radii between 18 000 and 110 000 km in good agreement with dip ingress timing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation